Inferior Temporal Conjunctival Autograft in Pterygium Surgery - Öksüz, Hüseyin; Tamer, Cengaver (Fırat University, 2006)
Objectives: To evaluate the results of pterygium excision surgery with inferior conjunctival autograft application. Materials and Methods: Twenthy-eight pterygiums of 27 patients that were excissed with autografts from inferior temporal quadrant under topical anesthesia with lidocaine gelly or local subconjuctival injection anesthesia were enrolled to the study. The postoperatif complications and recurrence rates were evaluated Results: Fifteen men and 12 women with a mean age of 47.7±11.57 were enrolled to the study. The mean follow-up period was 16.4±6.82 months. Recurrence was observed in 7.1% of the cases. Dellen formation was observed in 2 (7.1%) of the cases. Over reacting fibroblastic activity and thick fibrous tissue development was observed in 3 (10.7%) of the cases. Symblepharone formation was observed in 2 (7.1%) of the cases. Conculation: Pterygium surgery with autograft application from the inferior temporal quadrant results with post-operative complications not lower than the previously documented methods. However for the patients who are probabale candidate for future glaucoma surgery this technique as it well protects the superior quadrants may be applied. ©2006, Fırat Üniversitesi, Tıp Fakültesi

Amaç: İnferior konjonktival otogreft yöntemi ile yapılan pterjium cerrahisinin etkinliğini araştırmak. Gereç ve Yöntem: Primer piterjiumu olan 27 hastanın 28 gözüne topikal jel anestezisi veya subkonjonktival anestezi altında piterjium eksizyonu ve alt temporalden alınan konjonktival otogreft transplantasyonu yapıldı. Hastalar postoperatif komplikasyon ve nüks açısından değerlendirildi. Bulgular: 27 hastanın 12 tanesi kadın 15 tanesi erkekti. Hastaların yaş ortalaması 47.7±11.57 yıldı. Hastalar ortalama 16.4±6.82 ay takip edildiler. Nüks %7.1 oranında görüldü. İki olguda donör sahada dellen oluştu (%7.1). Üç olguda donör sahada fibröz doku oluştu (%10.7). İki olguda %7.1 sembleferon gelişti. Sonuç: Bu yöntemle yapılan piterjium operasyonlarında komplikasyon oranı yönteme göre yerine klasik otogreft yöntemine göre daha iyi değil, ancak ilerde glokom operasyonu olma ihtimali bulunan hastalara uygulanabilir. ©2006, Fırat Üniversitesi, Tıp Fakültesi
Piterjium Cerrahisinde Alt Temporal Konjonktival Greft Uygulaması